2020
DOI: 10.1186/s12889-020-08594-9
|View full text |Cite
|
Sign up to set email alerts
|

Effective methods for reactivating inactive blood donors: a stratified randomised controlled study

Abstract: Background Recruiting of sufficient numbers of donors of blood products is vital worldwide. In this study we assessed the efficacy and cost-effectiveness of telephone calls and SMS reminders for re-recruitment of inactive blood donors. Methods This single-centre, non-blinded, parallel randomised controlled trial in Guangzhou, China included 11,880 inactive blood donors whose last donation was between January 1 and June 30, 2014. The donors were ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…The use of SMS has increased among BCAs, with previous research demonstrating the effectiveness of a postdonation SMS notifying donors of the location to which their blood has been dispatched 27,28 . Like emails, SMS reminders are cost‐effective, and have been found to have a similar effect to telephone calls in encouraging donors to return 29 . Our study found support for the use of either SMS or email to notify donors their deferral was ending.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The use of SMS has increased among BCAs, with previous research demonstrating the effectiveness of a postdonation SMS notifying donors of the location to which their blood has been dispatched 27,28 . Like emails, SMS reminders are cost‐effective, and have been found to have a similar effect to telephone calls in encouraging donors to return 29 . Our study found support for the use of either SMS or email to notify donors their deferral was ending.…”
Section: Discussionsupporting
confidence: 51%
“…27,28 Like emails, SMS reminders are cost-effective, and have been found to have a similar effect to telephone calls in encouraging donors to return. 29 Our study found support for the use of either SMS or email to notify donors their deferral was ending. Interestingly, deferred donors responded more positively to a nonemotive message than to an emotive message; the latter including a photograph and story about a blood recipient.…”
Section: Discussionmentioning
confidence: 53%
“…3,16 Further, in a randomized controlled study by Ou-Yang J et al, 30.6% of self-reported deferral reasons accounted for medical reason. 27 In our center, hypertension happened to be an incidental finding for a few first-time donors, and was referred to a physician for further management. Earlier intervention in these donors can prevent complications and increase their likelihood of returning to the donor pool in the future.…”
Section: Medical Examination-based Deferralmentioning
confidence: 96%
“…Reminders through personalized letter, SMS, e-mail or telephonic conversation have been found to work successfully [ 36 , 52 – 54 ]. Telephonic communication has been observed to have a better return rate, but SMS services were found to be more cost-effective with a better contact rate [ 55 ]. Easing the process of donation: Time constraint has been the most common reason given by the TDD for not donating blood again [ 56 ].…”
Section: Factors Affecting Return Of Tddmentioning
confidence: 99%